Computer modeling of the castings shrinkage porosity with different metal supply on the basis of Navje-Stock’s equations - A. N. Chichko; S. G. Lihouzov; Ju. V. Jatskevich; O. I. Chichko (Литьë и металлургия)
There is offered the approach, based on the Navje-Stock*s equations, for calculation of sponginess, forming during the process of crystallization and cooling of the three-dimensional casting, having gating system. There are carried out the computer calculations of sponginess forming in the casting space “cross” for different variations of metal supply.